Determination of molecular weights of biologically active fragments of colostrum by electrophoresis method - Lych (Tkachenko), Inna; Veriovka, Serhii; Voloshina, Iryna (My University, 2017)
It has been determined that high molecular weight fractions of colostrum contain protein molecules with molecular weights of 160-190 kDa, among which are immunoglobulins. Separate parts of immunoglobulins and other proteins, namely, IgG (55kDa) and IgA (62kDa) heavy chains, secretory component of sIgA, and lactoferrin, have also been found out. The test samples of high molecular weight peptides of colostrum contain the biologically active fragments among which there are mostly immunoglobulins, their parts, proteinsabzymes, other protein fragments. The proteins with the molecular weight of 80, 62, 55 kDa are also determined, they can represent heavy chains (55 kDa) and light chains (25 kDa) of IgG and sIgA. In particular, sIgA is a supermolecular complex consisting of Н- and L-chains of IgA (62, 25 kDa, respectively) and a secretory component (80 kDa). Apart from the secretory component of IgA, the protein molecules with the molecular weight of 80 kDa can be halves of the molecules of immunoglobulins or lactoferrin.

Наявність великої кількості білків дає змогу використовувати молозиво: у виробництві дитячого, функціонального, лікувального та профілактичного харчування; у біотехнології при виробництві інших продуктів харчування спеціального складу; у медицині і фармакології для виготовлення харчових оболонок і капсул для лікарських речовин, біологічно активних та харчових добавок.
Keywords: кафедра біотехнології і мікробіології; colostrum; protein; immunoglobulin; electrophoresi; immunity; молозиво; високомолекулярні білкові фрагменти; імуноглобуліни; електрофорез; імунітет